The role of the breast care nurse during treatment for early breast cancer: the patient's perspective. - Halkett, Georgia (eContent Management Pty Ltd, 2006)
INTRODUCTION: Women who are diagnosed with breast cancer require the support of a range of people during their treatment. Although the role of the breast care nurse in providing support has recently been investigated in several Australian studies the patients' perspective on the role of the breast care nurse in Australian hospitals has not previously been described in detail. The aim of this paper is to explore patients' perspectives on the role of the breast care nurse. METHODS: In-depth interviews were conducted with 18 women who had completed treatment for early breast cancer. The women were asked to describe their experiences from the time of diagnosis through to treatment completion. Thematic analysis was used to analyse the data. FINDINGS: Breast cancerv patients repeatedly emphasised the importance eif the role eif their breast care nurses throughout their experience of breast cancer. The support that breast care nurses provided incorporated the following components: communication, rapport and an awareness of the women's needs, availability, reassurance and practical information. CONCLUSION: This study provides an understanding of women's perspectives on the role of breast care nurses and confirms that breast care nurses play an important support role during the experience eif early breast cancer. Oncology clinics should focus on ensuring that all women who are diagnosed with breast cancer have adequate access to the support that breast care nurses are able to provide.